Influence of Step Frequency on the Dynamic Characteristics of Ventilation and Gas Exchange During Sinusoidal Walking in humans - Fujita, Mako; Kamibayashi, Kiyotaka; Aoki, Tomoko; Horiuchi, Masahiro; Fukuoka, Yoshiyuki (Frontiers in Physiology, 2022)
We tested the hypothesis that restricting either step frequency or stride length cause the depression in ventilatory response with constrained breath frequency during sinusoidal walking. Thirteen healthy male and female volunteers (mean ± SD: age 21.5 ±1.8 yrs, height 168±7 cm, weight 61.5 ±8.3 kg) participated. The walking speed was sinusoidally changed between 50 m·min−1 and 100 m·min−1 with periods from 10 to 1 min. With the use of a customized sound system, we fixed the step frequency (SF) at 120 steps·min−1 with stride length (SL) variation (0.83 m to 0.41 m) (SFfix) or fixed the SL on 0.7 m with SF variation (143 to 71 steps·min−1) (SLfix) during the subjects’ sinusoidal walking. The control condition was the subjects’ preferred locomotion pattern without a sound system (Free). The control condition was the unprompted spontaneous locomotor pattern for each subject (Free). We measured breath-by-breath ventilation [tidal volume (VT) and breathing frequency (Bf)] and gas exchange [CO2 output (VCO2), O2 uptake (VO2)]. The amplitude and the phase shift of the fundamental component of the ventilatory and gas exchange variables were calculated. The results revealed that the SFfix condition depressed the amplitude of the Bf response compared to SLfix and Free conditions. Notably, the amplitude of the Bf response under SFfix was constrained by less than one breath at the periods of 5 and 10 min. By contrast, the SLfix condition resulted in the larger amplitudes of Bf and VE responses as well as Free. We thus speculate that the steeper slope of the VE-VCO2 relationship observed under the SLfix might be attributable to the central feed-forward command or upward information from afferent neural activity by sinusoidal locomotive cadence. The phase shifts of the VE, VO2, and VCO2 responses were unaffected by any locomotion patterns. Such sinusoidal wave manipulation of locomotion variables may offer new insights into the dynamics of exercise hyperpnea.